(untitled) (Global Journal of Medical Research, 2023)
Laparoscopic cholecystectomy LC is the most common elective laparoscopic procedure performed globally and is the gold standard treatment for gallstone disease A double gallbladder GB with or without duplication of cystic duct is a very rare surgical encounter with an incidence of approximately 1 in 4000 5000 population Symptomatic conditions of duplicated gallbladder are usually associated with cholecystitis cholangitis gallstone disease and pancreatitis but are rarely diagnosed with carcinoma Surgery is the ideal treatment choice of symptomatic duplicated gallbladder Duplication of the GB is rarely detected preoperatively can lead to difficulties during surgery with increased likelihood of conversion to open surgery and complications Our patients is a 45-year-old woman admitted as case of symptomatic cholelithiasis Patient was admitted to the hospital for laparoscopic Cholecystectomy